CARBOHYDRATES, PHENOLIC COMPOUNDS AND ANTIOXIDANT ACTIVITY IN PULP AND PEEL OF 15 BANANA CULTIVARS - AQUINO,CÉSAR FERNANDES (Sociedade Brasileira de Fruticultura, 2016)
ABSTRACT The aim of this study was to quantify and compare the levels of carbohydrates and phenolic compounds and the antioxidant activity in the pulp and peel of 15 banana cultivars in two ripening stages. Four bunches per cultivar were harvested in the pre-climacteric stage, six fruits were used by sample unit. Fruits were analyzed in the pre-climacteric stage and after ripening. Total, reducing and non-reducing soluble sugars, starch, phenolic compounds and antioxidant activity were evaluated. Cultivar and ripening stage influenced all characteristics analyzed. Unripe pulp and peel had small percentage of sugar, but high percentage of starch, especially ‘Terrinha’ and ‘Marmelo’ cultivars. AAB and ABB cultivars presented the highest percentages of starch, when compared to AA and AAA cultivars. For the phenolic compounds, the highest content was observed in ripe peel, followed by ripe pulp and unripe peel and pulp, highlighting ‘Terrinha’ cultivar in all parts and stages evaluated. The antioxidant potential was higher in ripe peel, followed by unripe peel, ripe and unripe pulp. Fruits of Terrinha, Marmelo, Maçã, Ouro and Caru-Verde cultivars showed the highest carbohydrate contents, and phenolic compounds or antioxidant activity, justifying future actions in the expansion of planting and consumption of these fruits.